Variation in Female Leverage: The Influence of Kinship and Market Effects on the Extent of Female Power Over Males in Verreaux’s Sifaka - Lewis, Rebecca J.; Bueno, Gabrielle L.; Di Fiore, Anthony (Frontiers in Ecology and Evolution, 2022)
Female mammals employ reproductive strategies (e.g., internal gestation) that result in power asymmetries specific to intersexual dyads. Because the number of eggs available for fertilization at any given time for most mammals is quite limited, having a fertilizable egg is potentially an important source of economic power for females. Control over mating opportunities is a source of intersexual leverage for female Verreaux’s sifaka (Propithecus verreauxi). We examined economic factors thought to influence the value of mating opportunities, and, thus, the extent of female leverage: kinship and market effects. Using a longitudinal dataset of agonistic interactions collected during focal animal sampling of all adult individuals in 10 social groups from 2008-2019, we tested the effects of relatedness, female parity, reproductive season, and adult sex ratio (population and group) on (1) the direction of submissive signalling and (2) which sex won a contested resource. While 96% of the acts of submission were directed from males towards females, females only won a third of their conflicts with males. Thus, our study has implications for evolutionary explanations of female-biased power. If female power evolved due to their greater need for food and other resources, then intersexual conflicts would be expected to result in males more consistently relinquishing control of resources. As expected, males were more likely to chatter submissively towards successful mothers, during the mating season, and when the sex ratio was male-biased. Although females generally had less power to win a conflict when their fertilizable egg was less valuable (when they were nulliparous or unsuccessful mothers or when interacting with male kin) and with an increasing female-bias in the sex ratio, this ability to win additionally was influenced by which sex initiated the conflict. Our study demonstrates that female leverage can be influenced by the supply and demand for mating opportunities, but evoking submission does not translate into winning a resource. Indeed, intersexual power is dynamic, contextual, and dependent on the individuals in the dyad.